If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -4y = 44 Solving 7x + -4y = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4y' to each side of the equation. 7x + -4y + 4y = 44 + 4y Combine like terms: -4y + 4y = 0 7x + 0 = 44 + 4y 7x = 44 + 4y Divide each side by '7'. x = 6.285714286 + 0.5714285714y Simplifying x = 6.285714286 + 0.5714285714y
| 6(n-9)=42 | | (3u+7)(2-u)=0 | | 3x^2+27x+54=0 | | 11x^2-77=0 | | 4x+10-6x=2x-19 | | 6T-9=4T-2T | | 2x^2+6x+3=0 | | 2x+5=13y | | 12x^3-27x^2-27x= | | -28+44= | | 2(x-6)=8 | | 3(3n+4)-2=5(n-1)-9 | | 8x+39=2x-15 | | 13y+5+2x= | | 15*x^3+30*x^2-65x-15=0 | | -3a=-12 | | 8a+5+11=0 | | 7p+15p= | | 5y-13=2 | | 3x+-2=-15 | | 12+6(z-2)=5z+1 | | 13-5y+2x= | | 11y+16z+24z+8y= | | 5x+2=35 | | g(x)=x^3+4x^2+7x+28 | | .8R+1=.08R+1.54 | | -9c-3b+15c= | | -6x=24 | | (-6+3r)+-1(r+4)=-2(r+-4) | | 8x+3-5x= | | 3(r-2)-(r+4)=-2(r-4) | | 4e-16=2e |